Annual report 2012 - (:unkn) unknown (Publications Office of the European Union, 2013)
Cedefop's annual report is intended as a presentational and accountability tool to help stakeholders and the general public to understand Cedefop's priorities and specific objectives, its main output and outcomes of its work. Information on each project is presented in a standard format, to make it easier to monitor and review projects' implementation. The issue 2012 gives an overview of Cedefop's key achievements in 2012. The second part monitors Cedefop's performance and monitors the implementation of the work programme 2012 by medium-term priority, actvity and project. (BIBB-Doku)
Keywords: S 3.5.5.1 CEDEFOP; I 1.5 Internationale Organisationen & Institutionen; I 2.2 Europa; CEDEFOP; Berufsbildungsforschung; EU-Bildungspolitik; Europäische Union; 2012